2021
DOI: 10.17648/acta.scientiae.6389
|View full text |Cite
|
Sign up to set email alerts
|

Criteria That Guide the Professor's Practice to Explain Mathematics at Basic Sciences Courses in Engineering Degrees in Peru. A Case Study

Abstract: Background: Research on mathematics teaching in basic science classes within Peruvian engineering degrees was required prior to the identification of alternatives to improve the training of future engineers. Objective: To identify the criteria that guide the practice of professors in Peru when explaining mathematics in basic science classes within engineering degrees, with specific reference to derivatives. Design: Qualitative case-study research that seeks to understand current mathematics teaching through an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Additionally, engagement with mathematics promotes critical reasoning, decision-making, metacognition, among many other skills (Saha et al, 2020), all of which are imperative for success in today's rapidly changing world (Said et al, 2023). Particularly, two of the most important are procedural and problem-solving skills, and although efforts to enhance the teaching of mathematics are ongoing worldwide, including in Peru, where the existing mathematics education model in schools and universities is being examined for potential transformation and improvement (Garcés-Córdova & Font-Moll, 2022;Garcés Córdova et al, 2021;Maraví Zavaleta, 2021), recent studies revealed that the development of mathematical skills still requires a long process of improvement (Faulkner et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, engagement with mathematics promotes critical reasoning, decision-making, metacognition, among many other skills (Saha et al, 2020), all of which are imperative for success in today's rapidly changing world (Said et al, 2023). Particularly, two of the most important are procedural and problem-solving skills, and although efforts to enhance the teaching of mathematics are ongoing worldwide, including in Peru, where the existing mathematics education model in schools and universities is being examined for potential transformation and improvement (Garcés-Córdova & Font-Moll, 2022;Garcés Córdova et al, 2021;Maraví Zavaleta, 2021), recent studies revealed that the development of mathematical skills still requires a long process of improvement (Faulkner et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Peruvian universities, the current state of mathematics education does not appear to be much better. While the continuous development of the Peruvian mathematics curriculum owes much to the efforts of educators and researchers engaged in scientific educational research (Maraví Zavaleta, 2021), there remains a noticeable lack of research in mathematics education within degree programs in Peru (Garcés Córdova et al, 2021). Additionally, Garcés Córdova et al (2021) have recently found that fundamental science courses are primarily delivered through a lecture-based and procedural approach, lacking innovations, realworld applications, and modeling.…”
Section: Mathematics Teaching In Perumentioning
confidence: 99%
See 2 more Smart Citations
“…Several empirical research works have been conducted employing the didactic suitability criteria to analyze lesson design and teaching practices in mathematics teacher education courses (Breda et al, 2017;Garcés et al, 2021). These investigations reveal the usefulness of TDS to recognize that the value judgments issued by teachers on the quality of their practices correspond to TDS criteria in some facets, but do not mention systematically all its facets and components.…”
Section: Implications Of Tds For Mathematics Teacher Educationmentioning
confidence: 99%